Follow-Up Treatment After Inpatient Therapy of Patients With Unipolar Depression—Compliance With the Guidelines? - Weiß, Lukas; Zeeck, Almut; Rottler, Edit; Weiß, Heinz; Hartmann, Armin; von Wietersheim, Jörn; , The INDDEP Study Group (Frontiers in Psychiatry, 2020)
Objective To date, there is only a limited number of studies evaluating the implementation and effects of treatment guidelines. Therefore, this study aimed to determine how many patients diagnosed with a major depression were treated in compliance with the German treatment guideline after hospital treatment, and whether a deviation from the guideline resulted in a less favorable development. Methods Five hundred two patients, which originally participated in the INDDEP-study, were included. Data were collected at admission and discharge from eight different psychosomatic (psychotherapeutic) hospitals in Germany as well as 3 months and 1 year after hospital treatment. Data on depressive symptomatology were assessed by QIDS-C (clinical interviews). By phone interviews, the clinical course and the outpatient treatments were assessed. Statistical analyses compared patients who were treated in compliance with the German treatment guideline with those who were not. Results Seventy-nine point one percent of the outpatient treatments complied with the treatment guideline. Eleven point eight percent of the patients were treated with medication only, 60.2% with psychotherapy only, and 28.0% with a combination. There was no difference in the clinical outcome (depression) with regard to guideline compliance. Cases in which deviation from the guideline occurred (20.9%) were younger and had a less severe depressive symptomatology at admission and after hospital treatment. Conclusion After treatment in a psychosomatic hospital or day hospital, the majority of patients with a depressive disorder received adjacent treatment in accordance with the German guideline and with a clear focus on psychotherapy. Deviations from the guideline did not result in a less favorable course of the illness. Clinical Trial Registration ISRCTN20317064, retrospectively registered 31.07.2012